Pengaruh Penerapan Model Pembelajaran Problem Based Learning (PBL) Terhadap Hasil Belajar Siswa Materi Sumber Daya Alam Kelas IV di SD Negeri 193 Palembang - Agustina, Oni; Arafat, Yasir; Tanzimah, Tanzimah (ANTHOR: Education and Learning Journal, 2022)
This study aims to determine the effect of applying the problem-based learning model to the learning outcomes of natural resource material for class IV SD Negeri 193 Palembang. The effect of the intended application in terms of student learning outcomes as long as the problem-based learning model is applied, the learning outcomes achieved after carrying out learning using the application of the problem-based learning model, the research subjects, namely class IV totaling 25 people with 16 male students and 9 female students, which will be given treatment using the Problem Based Learning model in natural resource science subjects. The method used is an experimental method with the type of One Group Pretest And Posttest. The data collection technique used the test method, and the data analysis technique used descriptive statistics. The results of the calculation of the initial test (pretest) obtained an average value of 46.6 while the final test (posttest) obtained 81.2 and the overall average value of Product Moment, namely rxy, was obtained at 0.567 which is included in the category "Moderate Positive ”. This shows the results of inferential statistical analysis using Product Moment correlation obtained rxy = 0.567 ≥ rtable = 0.396 there is a significant correlation even though the correlation is moderately positive from tcount = 5.966 ≥ ttable = 2.3 and n = 23 with a significant level of 32.1% so that Ho is rejected and Ha is accepted, meaning that there is a significant influence of the Problem Based Learning (PBL) learning model on student learning outcomes in class IV natural resource material at SD Negeri 193 Palembang.